Traumatic posterior atlantoaxial dislocation without related fractures of C1-C2 - Kambali, Maruti (Medknow Publications & Media Pvt Ltd, 2013)
Posterior dislocation without any associated fracture of odontoid is exceedingly rare and only 11 cases have been reported so far. A 32 year old male presented with pain, stiffness in neck, difficulty in breathing, associated lacerations on face and deformity of mandible and inability to open mouth. His plain radiographs, CT scan, MRI demonstrated a posterior dislocation of the atlas with respect of axis and a flake of bone from odontoid process on CT scan. He was successfully managed by closed reduction, C1C2 lateral mars pedicular screw stabilization and inter facetal fusion with synthetic bone graft substitute. At 10 months followup he had lost only 30° cervical rotation. The case is reported in view of rarity and to discuss the treatment rationale.